The real Metaphysical Club : the philosophers, their debates, and selected writings from 1870 to 1885 - Ryan, Frank X.; Butler, Brian E. (Professor); Good, James A. (James Allan) (SUNY series in American philosophy and cultural thought., 2019)
"The Metaphysical Club, a gathering of intellectuals in the 1870s associated with Harvard, is widely recognized as the crucible where pragmatism, America's distinctively original philosophy, was refined and proclaimed. Louis Menand's bestseller about the group was a dramatic publishing success. However, only three actual members - Oliver Wendell Holmes Jr., Charles S. Peirce, and William James - appear in this book, alongside other thinkers such as John Dewey who were never in the Club. The Real Metaphysical Club tells the full story of how this influential group shifted the course of philosophy in America. In addition to pioneering pragmatism, the group explored radical empiricism and idealism, and formulated personalism and process philosophy, equally important developments. This volume contains thirty-seven important writings dating from 1870 to 1885 by the real members of the Metaphysical Club. The first section centers on pragmatism and science; the second part collects writings of the lawyers; and the third part covers idealist and personalist philosophers. Many of these writings have never been reprinted before, and nothing like this impressive collection has ever been attempted. A general introduction provides a narrative history, and the editors' three introductions to the volume's sections vividly bring to life the intense meetings, sustained debates, and pioneering thought from the Metaphysical Club"--